The Enhanced Performance of Phase-Change Materials via 3D Printing with Prickly Aluminum Honeycomb for Thermal Management of Ternary Lithium Batteries - Ming Cao; Juhua Huang; Ziqiang Liu (Advances in Materials Science and Engineering)
This study introduces a new type of lightweight, shape-stable composite phase-change material (CPCM) to improve the thermal management of ternary lithium batteries. Paraffin wax (PW) was used as a phase-change material, expanded graphite (EG) and high-density polyethylene (HDPE) were used as support materials, carbon fiber (CF) was used as a heat-conductive additive, and a 3D printed aluminum honeycomb with a prickly structure (3D Al-Hc) was added to enhance the mechanical properties and thermal conductivity of the CPCM. The properties of the CPCM were analyzed based on its microstructure, thermal properties, and stress-strain response. The CPCM was applied to a battery cooling module to determine the temperature response of a battery. The results showed that when the CF mass fraction was 4.5 wt%, the degree of supercooling in the PW/EG/CF/HDPE was reduced by 51.5% and 43.3% compared to PW PCM and PW/EG CPCM, respectively. In addition, the thermal conductivity of the PW/EG/CF/HDPE/3D AL-Hc CPCM (5.723 W/(m·K)) was 1.9 times that of the PW/EG. Due to the presence of the 3D AL-Hc, the CPCM has a strain of 1.25 mm at a pressure of 100 KPa. In addition, the CPCM has excellent battery thermal management performance. At a 2.5°C discharge rate, the operating temperature of the battery is kept within the safe temperature range of 50°C.